2016
DOI: 10.1021/acs.langmuir.6b01482
|View full text |Cite
|
Sign up to set email alerts
|

Phase Transitions in Dipalmitoylphosphatidylcholine Monolayers

Abstract: A self-assembled phospholipid monolayer at an air–water interface is a well-defined model system for studying surface thermodynamics, membrane biophysics, thin-film materials, and colloidal soft matter. Here we report a study of two-dimensional phase transitions in the dipalmitoylphosphatidylcholine (DPPC) monolayer at the air–water interface using a newly developed methodology called constrained drop surfactometry (CDS). CDS is superior to the classical Langmuir balance in its capacity for rigorous temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
59
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 37 publications
(101 reference statements)
7
59
0
Order By: Relevance
“…Different regions in the P-A isotherms are attributed to various phases and their coexistence regions of the corresponding Langmuir monolayers: a horizontal line in the P-A isotherm is interpreted as the first-order G-LE phase coexistence regime, 9,11 or a G-LC phase transition for temperatures below the G-LE-LC triple point, 12,13 whereas a non-horizontal line is found to exist for coexistence of condensed phases. 7 The formation of 2D surface micelles, 2,3,7,14,15 which has been observed experimentally by using e.g. fluorescence microscopy, is found to be the main reason for the non-horizontal line in P-A isotherms.…”
Section: Introductionmentioning
confidence: 73%
“…Different regions in the P-A isotherms are attributed to various phases and their coexistence regions of the corresponding Langmuir monolayers: a horizontal line in the P-A isotherm is interpreted as the first-order G-LE phase coexistence regime, 9,11 or a G-LC phase transition for temperatures below the G-LE-LC triple point, 12,13 whereas a non-horizontal line is found to exist for coexistence of condensed phases. 7 The formation of 2D surface micelles, 2,3,7,14,15 which has been observed experimentally by using e.g. fluorescence microscopy, is found to be the main reason for the non-horizontal line in P-A isotherms.…”
Section: Introductionmentioning
confidence: 73%
“…It is worth mentioning that several recent studies [38][39][40] warned about possible problems with some of these experimental methods. Thus, it was shown that Langmuir trough-based techniques may give unreliable results for the reversibility of the surface phase transitions, when reaching low surface tensions, due to the leakage of material [38]. An approach to overcome this problem was proposed in [39] where reversible phase transition in phospholipid layers was studied by a new method, called "constrained drop surfactometry", which is claimed to provide a leakage-proof environment.…”
Section: Figurementioning
confidence: 99%
“…To model different respiration conditions, we xed the surface tension to 30 mN m À1 and 10 mN m À1 , respectively. 40,41 MD simulations suggested that the pristine SWCNTs can insert into, translocate across or be wrapped by the PSM, depending on the tube size and PSM tension. Specially, ultrashort SWCNTs with lengths comparable to the monolayer thickness (L ¼ 1.25 nm) were found to vertically insert into the PSM, regardless of the PSM tension ( Fig.…”
Section: Pristine Swcntsmentioning
confidence: 99%